PENGARUH NILAI TUKAR, SUKU BUNGA, INFLASI, JUMLAH UANG BEREDAR DAN PDB TERHADAP INDEKS HARGA SAHAM GABUNGAN (IHSG) PERIODE 2005-2015 - Otorima, Mone; Kesuma, Ali (Jurnal Terapan Manajemen dan Bisnis, 2016)
This study examined the effect of exchange rates, interest rates, inflation, money supply, gross domestic product and the global crisis on IHSG. The analytical method used in this research is multiple linear regression analysis. Sample studies using daily data from 2005 to 2015.Â  The results of this study indicate that the depreciation of the exchange rate, the decline in gross domestic product, growth in the money supply and the global crisis negatively affect the IHSG, while the variable gross domestic product increase positive influence on IHSG.